Numerical Modeling of Dynamic Soil-Structure Interaction in Bridges with HP Driven Piles (47ff630e-35bf-41f4-946a-236631b70ac5) - Yu Bao; Andrew Rietz; Steven Halewski (Deep Foundations Institute, 2017)
"HP-Pile foundations are the most favorable type of foundations for bridges because of their constructability, versatility with regard to subsoil conditions, and settlement controllability. For many years, bridge engineers have puzzled over the most economical way to orient HP-Piles: Should the strong axis be oriented in the longitudinal direction or in the transverse direction? The accurate design of foundations may considerably reduce construction costs. In order to answer this question, 3-D finite element models will be set up to analyze the effects of pile orientation on bridge behavior. Because seismic loading usually controls the structural design in seismic zones, it is important to investigate the effects of pile orientation under such loading. HP-Piles are designed conservatively due to the uncertainty of the dynamic soil-structure interaction during earthquakes. For the bridge substructure, the soil’s stiffness plays an important role in load distribution as the soil and piles act as a combined system to resist the seismic loading. The dynamic soil-structure interaction mechanisms of bridges in both the longitudinal and the transverse directions will be investigated through the use of 3-D finite element models. The numerical models will realistically simulate the soil-pileabutment- wingwall-superstructure system subjected to seismic loads. Nonlinear soil springs will be employed to model the non-elastic soil behavior. The analysis will provide theoretical support to the design practice.IntroductionAs sustainability has asserted itself in the public’s eye, bridge professionals have rushed to develop criteria for sustainable bridges. The three main categories that define and distinguish sustainable bridges are: lower energy input, increased durability, and simplified deconstruction. By optimizing the structural members, the engineer is able to reduce the material quantities for the bridge, effectively reducing the energy input for the bridge (Hunt; Whittemore). A deeper understanding of soilfoundation- structure mechanism will facilitate sustainable bridge design by lowering energy input and increasing the service life of bridges (Rietz et al.)."